Predicting the Risk of Type B Aortic Dissection Using Hemodynamic Parameters in Aortic Arches: A Comparative Study between Healthy and Repaired Aortas. (March 2023) - Wen, Jun; Huang, Haodi; Su, Zhiqiao; Jiang, Linke; Gao, Qi; Chen, Xiaoyi; Yan, Tingli; Peng, Liqing
Highlights: Both pathological anatomical features and hemodynamic indicators may be changed before the TBAD occur. Hemodynamic indicators may be more accurate in predicting the risk and location of TBAD. Averaged OSI and CFI index may be significantly enhanced in the region where the entry tears have appeared before the TBAD occur. As a new WSS-based indicator, TSVI was more sensitive to the marked tortuosity, which may have the potential to predict the risk of TBAD. Abstract: Background and objective: The development of acute aortic dissection (AD) remains unpredictable due to the intricate nature of the AD mechanism and the varied patient-specific aortic anatomy. The aim of this study was to simulate the hemodynamic parameters in the aortas before the onset of TBAD with healthy controls. Methods: This study numerically assessed the effectiveness of hemodynamic indicators in predicting the risk of type B AD (TBAD) by investigating the differences in hemodynamic parameters between healthy and repaired aortas (aortas before TBAD development). Four wall shear stress (WSS)-based indicators and three helicity-based indicators were adopted and analyzed. Results: The results showed that more pathological anatomical feathers can be observed in the repaired aortas. For WSS-based indicators, only averaged cross flow index (CFI) and oscillatory shear index OSI (CFI, 1.03 ± 0.07 vs. 0.83 ± 0.10 and OSI, 0.12 ± 0.03 vs. 0.04 ± 0.02) (all p <0.001) were significantly higher in the repaired aortas than those in the healthy aortas. On the other hand, average helicity in the repaired aortas also showed a significant difference compared with that in healthy aortas (h1, 3.88 ± 5.55 vs. -8.03 ± 14.16) ( p <0.05). Furthermore, the skewed helical structure and flow disturbance was found in the repaired aortas. Conclusion: 1) There are marked differences in pathological anatomical features, such as aortic dilation, elongation and tortuosity between the healthy aortas and repaired aortas, and the corresponding hemodynamic indicators also have also been significantly changed. 2) Compared with anatomical characteristics, hemodynamic indicators may be more accurate for predicting the risk and location of TBAD, such as the OSI and CFI index were significantly enhanced in the region where the entry tears have occurred. 3) In clinical practice, anatomical features remain important factors for assessing the risk for development of TBAD; however, hemodynamic analyses with quantitative data and more visualizing characteristics have showed promising potential in this aspect.